1991
DOI: 10.1021/jo00009a006
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective hydroxylation of steroids via oxometalloporphinates covalently linked to ring D: introduction of hydroxyl groups into the C(9) and C(12) position of 5.alpha.-androstanes

Abstract: 2957Brief illustrative experimental procedures serve to demonstrate the utility of these methods. First, treatment of 35 mmol of 5 with 50 mmol of LDA in 50 mL of THF for 2 h at 0 OC and hydrolytic workup gave a 96% yield of a 45:55 mixture of the cis and trans isomers of diphenyl-l-propenylamine (I 1). Although stoichiometric amounts of LDA are employed in this case, such isomerizations can be effected by catalytic amounts of LDA as well. Second, treatment of 20 mmol of 5 with 22 mmol of n-BuLi in 100 mL of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 1 publication
2
19
0
Order By: Relevance
“…3.1. Crystal structure description of (1) and (2) Crystallographic data and structural refinement details of (1) and (2) are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3.1. Crystal structure description of (1) and (2) Crystallographic data and structural refinement details of (1) and (2) are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Macrocycles of meso-tetrakis [4-(benzoyloxy) were prepared as previously described [36][37]. Scheme S1 gives the main steps of the preparation of (1) and (2).…”
Section: Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…"Meta"-substituted tetraphenylporphyrins attached to 5 -androstan-3 -ol derivatives have shown to lead to oxidation in the presence of PhIO [203]. Hydroxylations at either C(9) and/or C(12) of the steroid nucleus have been carried out by "ortho"-substituted porphyrins attached to the C(17) position of 5 -androstane [204]. The use of manganese(III) salen (N,N'-bis-(salicylideneamino)ethane) complexes attached to steroid substrates also mediated the hydroxylation of unactivated carbons with PhIO as the oxygen atom source [205].…”
Section: Remote Functionalizationmentioning
confidence: 99%
“…Grieco and colleagues (18)(19)(20) have also shown that a metalloporphyrin can hydroxylate a steroid in an intramolecular reaction if it is covalently attached, but again, this is not a catalytic process with turnover. We have now made a catalyst that indeed binds a substrate, performs a hydroxylation catalyzed by a metalloporphyrin, and then releases the product to perform true turnover catalysis.…”
mentioning
confidence: 99%